Canadian Laws Are on Target—But Is the Transplant Community?. Issue 4 (April 2017) - Rogers, Rodney L.; Stock, Peter G.
Abstract : With HIV-positive donor organs coming available, a careful assessment on allocation needs to include a balance of risks and benefits. While some geographic specificities may apply, the authors feel that that HIV-positive recipients benefit from receiving organs from HIV-positive donors.